Role of the Clergy of Vilnius St. John’s Church in the Life of the City’s Beggars in the 18th Century - Miškinytė, Rūta (Lietuvos istorijos studijos, 2022)
This paper examines an aspect of the functioning of the organization of Vilnius’ beggars that has not yet been sufficiently covered in the historiography: the role of the clergy of St. John’s Church in the life of the city’s beggars. This text focuses on the relationship between the clergy and the beggars during the 18th century. By using the personal documents of bishops, registers of the masses held in the church, and sources written by the beggars themselves or related to the aforementioned organization, it is shown that the clergy of Vilnius’ parish church not only took care of the spiritual needs of the beggars, but also looked after the finances of the organization and actively participated in its internal life, with their influence on the beggars manifesting itself in their personal relations with beggars beyond the scope of the organization.
Keywords: beggars; beggars’ organization; St John’s church; parish; Adam Ancypa; Antoni Konstantin Korwin-Kossakowski; Vilnius; 18th century